Delusion in death - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2012)
When a downtown bar erupts in sudden violence that leaves eighty people dead, Lieutenant Eve Dallas discovers that the bar's patrons were exposed to a lethal cocktail of chemicals and illegal drugs that a sinister killer administered through an airborne method.